2019
DOI: 10.3390/biom9040118
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Neuroprotective Effects of Aspirin, Atorvastatin, Captopril and Metformin in Diabetes Mellitus

Abstract: Objective: The aim of this study was to investigate the effect of combined intake of a high dose of aspirin, atorvastatin, captopril and metformin on oxidative stress in the brain cortex and hippocampus of streptozotocin (STZ)-induced diabetic rats. Material and methods: Rats were randomly divided into the following 11 groups: control and diabetic (D), as well as 9 groups that were treated with metformin (M, 300 mg/kg) or aspirin (ASA, 120 mg/kg) alone or in different combinations with captopril (C, 50 mg/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…These results contradict the literature that underlines the negative correlation between executive functions and aging [9]. However, they could be explained by the fact that many of the elderly participants reported taking metformin, aspirin, atorvastatin, and angiotensin converting enzyme inhibitors (ACEi) or ARBs, which, when taken as a combination, could potentiate the anti-oxidant effect of each drug, enhancing their neuroprotective effects on the hippocampus [44].…”
Section: Other Factorsmentioning
confidence: 57%
“…These results contradict the literature that underlines the negative correlation between executive functions and aging [9]. However, they could be explained by the fact that many of the elderly participants reported taking metformin, aspirin, atorvastatin, and angiotensin converting enzyme inhibitors (ACEi) or ARBs, which, when taken as a combination, could potentiate the anti-oxidant effect of each drug, enhancing their neuroprotective effects on the hippocampus [44].…”
Section: Other Factorsmentioning
confidence: 57%
“…Aspirin, statins, angiotensin converting enzyme II (Ang II) inhibitor, and metformin are commonly used in the secondary prevention of cardiovascular events and treatment of concomitant diseases; they also exhibit many pleiotropic effects [46]. The Paseban et al’s [47] study showed that the combined use of the above-mentioned drugs enhances their antioxidant effect. Aspirin has an antioxidant effect by reducing the production of free radicals, such as peroxide, and prevents a decrease in the activity of antioxidant enzymes (catalase and peroxide dismutase) [48].…”
Section: Discussionmentioning
confidence: 99%
“…Although preclinical studies using animal models suggest that aspirin can interfere in the development of insulin resistance, the results from human clinical trials are less convincing, with ASA alone having a lower effect on metabolic damage than combined therapy. For example, administration of aspirin combined with common diabetes medications potentiated their antioxidant effects and reduced oxidative stress [55]. Furthermore, the increased risk of gastrointestinal bleeding following administration of aspirin limits its use as long-term pharmacotherapy [56].…”
Section: Acetylsalicylic Acidmentioning
confidence: 99%